Pemanfaatan Teknologi Informasi Untuk Analisis dan Tindak Lanjut Hasil ANBK Dalam Manajemen Satuan Pendidikan Dasar (Lembaga Pengembangan Kinerja Dosen, 2025)
The use of information technology in basic education management is a strategic key in the analysis and follow-up of ANBK results. This study aims to explore the application of information technology in the context of managing ANBK results at SDN Ciawi, Tasikmalaya Regency. This research uses a qualitative research approach, data obtained through interviews, observations, and documentation of school principals, teachers, and school operators. The results of the study show that the use of digital platforms such as education report cards has been used to analyze the results of ANBK and design data-based follow-up programs. This helps obstacles such as low teacher literacy, limited infrastructure, and high dependence on the role of operators are still challenges. The results of this study provide an important overview of the need to strengthen human resource capacity, technology integration, and school work culture, as well as sustainable system support to improve the quality of data-based education at the elementary school level.